The role of organic solvent and nano-additives loading in preparing and characterizing graphene oxide based polystyrene nanocomposites - Mohammadsalih, Zaid G.; Uddin Siddiqui, Vasi; Sapuan, S. M. (Taylor and Francis Ltd., 2024)
In this work, two types of organic solvents: namely, dimethylformamide (DMF) and tetrahydrofuran (THF); were investigated individually to prepare graphene oxide (GO) based polystyrene (PS) nanocomposites. Both were effective exfoliation agents for GO nano-sheets using sonication process. However, DMF showed poor solubility for PS beads compared to THF due to its high boiling point, poor volatility, and the prevailing monomer–monomer interaction rather than monomer–solvent interaction. Hot pressing was not an efficient preparatory approach for those samples prepared by DMF. Hence, solution casting, and THF were adopted to prepare PS and its GO-based nanocomposites. (0.5 and 1.0) wt. % of GO were dispersed homogeneously in PS using different dispersive techniques. Range of properties were tested for the pure polymer and its GO-based nanocomposites prepared by THF. A good dispersion of GO nano-sheets in PS was observed by different microscopic techniques. A significant improvement of mechanical and thermo-mechanical (storage modulus) performances for the polymer nanocomposites (PNCs) were achieved compared to the pure polymer. Young’s modulus for PS/GO nanocomposites was improved by 122% and 143% for GO loadings of 0.5 and 1.0 wt. %; respectively, and storage modulus for the nanocomposites recorded a considerable promotion compared to the pure polymer.